The reproductive strategy of a typical distylous Ophiorrhiza alatiflora (Rubiaceae), in fragmented habitat - Li, Yu; Yao, Ren-Xiu; Xu, Bo; Liu, Yun-Jing; Li, Bai-Zhu; Tang, Ming; Yi, Yin; Wen, Zhi-Rui; Wang, Xiao-Yue; Tang, Xiao-Xin (Frontiers in Plant Science, 2024)
Heterostyly is a genetically controlled style polymorphism, that plays an important role in promoting outcrossing and improving reproductive fitness. Although distyly is often studied in plants of the Rubiaceae family, little attention has been paid to the reproductive strategies of distylous species in fragmented habitats. Here, We report for the first time the growth of Ophiorrhiza alatiflora, a type distylous species, in karst areas and evaluate its reciprocity between long-styled morph and short one. We analyze the two distyly morph differences in the ancillary polymorphic of flowers and explore their reproductive strategy in fragmented habitats. Our research indicates that O. alatiflora is a typical distylous plant for the distyly has high reciprocity. Both morphs exhibit the highest fruit set of intermorph outcrossing; The pollen germination and pollen tube elongation experiments have also demonstrated that the affinity of pollen from intermorph outcrossing is highest, regardless of whether it is the long or short morph as the maternal parent; Meanwhile, O. alatiflora is an incompletely self-incompatible plant that exhibits a certain degree of self-pollination and intramorph outcrossing, which may be one of the important means to ensure sustainable reproduction in severely disturbed habitats. In the ancillary polymorphic of flowers, L-morphs flowers produce more pollen, and S-morph flowers produce more ovules to improve their male-female fitness and compensate for the asymmetry of pollen flow; Compared with S-morphs, L-morphs contain significantly higher levels of several kinds of terpenoids. S-morphs produce more flavonoids than L-morphs. The differences in secondary metabolites between L-morphs and S-morphs are mainly reflected in the different nutritional organs (including stems and leaves). Overall, our work has revealed the unique reproductive strategy of O. alatiflora in fragmented habitats based on the characteristics of distyly, verifying the hypothesis that the distyly of O. alatiflora promotes outcrossing and avoids male-female interference, improving male-female fitness and this is the first time in the Ophiorrhiza genus.